Intra- and Inter-Day Reliability of Inertial Loads with Cluster Sets When Performed during a Quarter Squat on a Flywheel Device - Shane Ryan; Rodrigo Ramirez-Campillo; Declan Browne; Jeremy A. Moody; Paul J. Byrne (MDPI AG, 2023)
The aims of this study were to (i) estimate the intra- and inter-day reliability of mean concentric (CON) and eccentric (ECC) power at different inertial loads during a flywheel quarter-squat using a cluster set approach and (ii) to determine the acute effect of internal and external attentional focus on mean power when performing the flywheel quarter squat. Twelve collegiate field sport male athletes (age 22.4 ± 3.2 years, weight 81.4 ± 10.3 kg, height 1.81 ± 0.06 m) attended four cluster set testing sessions separated by 7 days. Sessions consisted of 4 sets of 15 repetitions using 4 inertial loads (0.025, 0.050, 0.075, and 0.100 kg·m2). A cluster block consisted of 5 repetitions, including "momentum repetitions" (4 × 5 + 5 + 5). Mean power (MP), CON power, ECC power, and ECC overload were recorded for both internal and external attentional focus groups. The external instructional group attained familiarization after two flywheel sessions (ES = 0.03-0.15) with little volatility between performance measures (CV% = 3.39-9.22). The internal instructional group showed large differences in MP output from session 2 to session 3 for all loads (ES = 0.59-1.25). In conclusion, the flywheel cluster set approach is a reliable training modality for maintaining MP output during all repetitions.